Towards integrated science education through collaborative project-based learning: Teachers’ perceptions, experiences and practices - Haatainen, Outi (LUMAT-B: International Journal on Math, Science and Technology Education, 2022)
Teachers have a pivotal role in implementing new research and science education reforms into classroom practices. Through focusing on teachers’ perceptions, experiences and practices, this thesis aims to understand how integrated science education (ISE) can be promoted at different education levels, especially by utilizing collaborative project-based learning (PBL). ISE is an effort to integrate science curriculum content into a meaningful whole by a constructive and context-based approach that crosses subject boundaries and links learning to the real world. It is a current issue amongst researchers and recent policy reforms (e.g., Finnish National Core Curriculum) due to the many promises it offers for increasing the relevance of science education which in turn can enhance students’ interest towards science subjects such as chemistry. For example, ISE can offer students a more integrated understanding of complex everyday life phenomena, increase students’ conceptual understanding and develop their transversal competencies (e.g., thinking, learning and communication skills). Student-centred and teacher-facilitated teaching methods such as PBL have been suggested for ISE. PBL organizes learning around clearly defined projects and engages students in collaboration and constructive investigations of authentic problems. Implementing ISE, especially beyond natural science subjects, is often a novelty to teachers. Not enough is known of teachers’ perceptions and self-efficacy beliefs regarding ISE. Furthermore, research has not sufficiently shown how ISE should be implemented. The aim of this thesis is to understand teachers’ perceptions, experiences and practices of ISE in order to better promote integrative practices at various educational levels by supporting teachers. Therefore, the qualitative-dominant mixed-method approach of this thesis focused on three questions: 1) How do science teachers perceive ISE and PBL? 2) What kind of experiences do science teachers have of integrated practices? 3) What kind of integrated practices do science teachers have? The research has mainly been conducted within teacher communities offered by LUMA Centre Finland and the international StarT programme since 2016. The questions have been answered through four interconnected studies (I-IV). Data for studies I and II were collected by a survey during a time, in which the integrated education policies were introduced to the Finnish educational system. Study I explores the art integration practices of science teachers (n=66). Study II elaborates how science teachers’ (n=95) perceptions of and experiences with integration influence their perceptions on self-efficacy related to ISE. Study III consisted of a qualitative-led survey (n=244) and a case study (n=12). It was conducted within the international StarT programme and aimed at understanding teachers’ perceptions and practices of PBL in science education. Last of the studies (IV) was a case study mapping out teachers’ (n=85) perceptions of the design principles of ISE. The data was collected from Finnish in-service teachers and pre-service teachers participating in an open online course focusing on integrated science and mathematics education and PBL as an integrated pedagogical approach. The results of this thesis offer new insights on teachers’ perceptions, experiences and practices of ISE and collaborative PBL at different educational levels. Teachers perceive ISE as a student-centred and context-based approach that requires, among other things, collaboration between subjects and links to students’ daily lives. Teachers perceive ISE and PBL as relevant but challenging to implement in practice, and their experiences and practices of ISE and PBL varied. Especially secondary school science teachers in Finland had little experience of ISE, interdisciplinary collaboration and PBL as an integrative teaching method. Teachers need support with the implementation of integrative approaches in science education, especially when integrating beyond natural science disciplines, such as arts integration with science. Supporting teachers through educational programmes such as the StarT programme and by providing feasible pedagogical models for ISE can have positive effects on teachers’ experiences, perceptions and self-efficacy beliefs. These affect teachers’ willingness to implement more ISE and PBL. For promoting ISE and the relevance of science education at various education levels, a novel pedagogical model for ISE was designed. The model includes five intertwined principles to be taken into account when implementing ISE: (1) form a coherent whole of the integrated lesson unit, (2) focus on the relevance of learning, (3) engage students in constructing knowledge, (4) include knowledge practices, and (5) use versatile instruction and assessment methods. The results can be applied from pre-service to in-service teacher education at all education levels, especially in chemistry education. In addition, results should be taken into account when designing a curriculum emphasizing ISE.